Development of Metacognitive Skills through Digital Narratives in Higher Education - Yuliana Lavrysh; Mariya Leshchenko; Larysa Tymchuk (Revista Electrónica de Investigación Educativa)
This paper focuses on metacognition facilitation through digital narratives. The objectives of the study were to explore how the creation of digital narratives strengthens the formation of metacognitive skills, and which teaching practices promote awareness of learning. The process of digital narrative creation connects literacy, language, technologies, and metacognitive planning, debugging, monitoring, and assessment strategies. A metacognitive awareness inventory questionnaire was used to assess the level of metacognitive skill formation, and content analysis and descriptive statistics were employed to analyze interviews and discussions. The study involved engineering and pedagogy students from three universities. Findings demonstrated improved metacognition subject to the implementation of appropriate teaching practices and the existence of an educational partnership between students and teachers. The most relevant practices were identified, and it was concluded that digital narratives may be an efficient strategy for the development of metacognitive skills including knowledge about cognition and regulation of cognition.